Community's Willingness to Participate in Wastewater Management in Aceh - Rohendi, Aulia; Faridy, Faizatul; Adinata, Budi Rahmat; Kadafi, Muhammad; Iqra, Alief Prasandi; Rahmawan, Iman (Department of Environmental Engineering - Universitas Pasundan - Indonesia, 2025)
Communal wastewater treatment plants (WWTPs) have been established in the Province of Aceh, mostly in Banda Aceh City as the capital and other parts of the province, to address significant environmental risks posed by wastewater originating from domestic activities. However, limited coverage, poor effluent quality, and insufficient community involvement persist. This research assesses public participation and willingness to engage in wastewater management practices. A quantitative survey was conducted with 148 Banda Aceh and Aceh Barat respondents, selected through multi-stage random sampling. The first stage in respondent selection is based on area. Banda Aceh City, the provincial capital, was chosen as the initial location for the respondents’ residence, followed by Meulaboh as the regency capital. The second stage involves respondents who have household businesses (which generate domestic waste, in this case, owners of laundry and vehicle washing businesses) and those who do not have businesses. The survey explored respondents' perceptions of environmental pollution, awareness of wastewater regulations, and their readiness to participate in management efforts. The findings reveal that 77.7% of respondents are willing to join in wastewater management initiatives, with 52.21% expressing a willingness to attend community meetings and 18.14% agreeing to pay fees for communal WWTP services. Key factors influencing participation include awareness of environmental issues, positive perceptions of communal WWTPs, and the belief that the government should provide wastewater treatment infrastructure. The study concludes that increasing public awareness and involving communities in policy formulation is crucial for improving wastewater management in Aceh. These insights can guide local governments in developing effective regulations and fostering sustainable community engagement in environmental protection efforts, potentially leading to a healthier and more sustainable environment for the people of Aceh.